1980
DOI: 10.1084/jem.151.5.1151
|View full text |Cite
|
Sign up to set email alerts
|

Role of alloantigens in natural killing. Allogeneic but not autologous tumor biopsy cells are sensitive for interferon-induced cytotoxicity of human blood lymphcoytes.

Abstract: Blood lymphocytes of patients with solid tumors were assayed for cytotoxicity against autologous and allogeneic primary tumor cells. The lymphocytes killed autologous tumor cells in 7 of 25 cases (28%) and allogeneic tumor cells in 2 of 37 tests (5%). Lymphocytes from healthy donors were rarely cytotoxic for the biopsy cells, which indicates that these cells have low natural kill sensitivity. The autoreactivity that may reflect the immunological recognition of tumor cells was not altered by pretreatment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…shown to augment NK activity and to stimulate lysis of allogeneic but not of autologous fresh tumors (33,34). Because IF is known to be present in PP-TCGF, we tested whether IF and not IL-2, as presumed, was the primary stimulus for LAK.…”
Section: Immune Interferon (If) Is Not the Primary Stimulus In Pp-tcgmentioning
confidence: 99%
“…shown to augment NK activity and to stimulate lysis of allogeneic but not of autologous fresh tumors (33,34). Because IF is known to be present in PP-TCGF, we tested whether IF and not IL-2, as presumed, was the primary stimulus for LAK.…”
Section: Immune Interferon (If) Is Not the Primary Stimulus In Pp-tcgmentioning
confidence: 99%
“…Fresh tumour cells from human neoplastic tissues are generally resistant to natural cytotoxicity as measured by conventional cytolysis assays (Pattengale et al, 1982;Serrate et al, 1982;Vanky et al, 1980;Verkmeister et al, 1979;Vose et al, 1977aVose et al, , 1977bVose et al, , 1978Vose & Moore, 1980;Zarling et al, 1979). In a study with various human tumours, mainly of mesenchymal origin, Vanky et al reported that IFN-induced killing of fresh biopsy cells only if allogeneic combinations of PBL and target cells were used (Vanky et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In a study with various human tumours, mainly of mesenchymal origin, Vanky et al reported that IFN-induced killing of fresh biopsy cells only if allogeneic combinations of PBL and target cells were used (Vanky et al, 1980). Killing of fresh leukaemic targets by normal allogeneic effectors was reported by Moore et al (1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A concentration of 30-120 units/well was used in NK assays. In vitro culturing of some tumour cells has been known to alter their susceptibility to NK (Vanky et al, 1980;de Vries et al, 1975 (Table I). However, IFN failed to induce any activity against the resistant Cx680.…”
Section: Interferonmentioning
confidence: 99%